Mapa das zonas de vizinhanças: tecnologia para encontros (im)possíveis no fazer políticas públicas de guardas municipais e articuladores da juventude em territórios vulnerabilizados de sobral - Silva, Thamila Cristina Santos da (2022)
The specific panorama of the intensification of violence, more precisely those expressed by homicides of adolescents and young people, is manifested in an expanded way in the Northeast region of Brazil. The Atlas of Violence (2016) and the Report of the Ceará Committee for the Prevention of Homicide in Adolescents (2016) describe that the State of Ceará had a 122,8% increase in the general rate of homicides in the period from 2005 to 2015, jumping from 1.699 to 4.163 deaths. This research is part of the problematic field of expressive lethal violence, as public policies in peripheral territories are affected by necropolitics that have repercussions on their agents. The tool-concept of necropolitics intersects this research, lining up topics and reflections. We work with theoretical references of training policies and the philosophy of difference in intercession with cartographic perspectives that relate training policies, territories and subjectivation. It is discussed based on a proposal for training in human rights produced by the Unit for the Management of Violence Prevention Projects (UGP-PV) with municipal guards and youth articulators who work in peripheral territories of Sobral-CE. Methodologically, an intervention research was chosen to build with three policy agents an artistic-political device called a map of neighborhoods, having as a starting point the formations experienced in the UGP-PV: two with municipal guards in the year 2019, accompanied by the researcher in the condition of trainer and a training experienced by youth articulators in the same unit, but under a different curricular matrix in the year 2018. We considered for analysis the process of construction of the device with guards and articulators and the analyzing questions that emerged in this path that problematize demands for the formation and the daily ways of acting in facing necropolitics. As a technical product of this research, we created an artistic-political formative device, the neighborhood zone map, which analyzes formative issues experienced by these agents and can be a reference for future formations that put differences in dialogue.